In the right place at the right time: analysis of p53 serine 312 phosphorylation in vivo - Slee, EA; Lu, X (Taylor and Francis, 2011)
Comment on: Slee EA, et al. Proc Natl Acad Sci USA 2010; 107:19479–84.